Gray Markets and Multinational Transfer Pricing - Autrey, Romana L.; Bova, Francesco (The Accounting Review, 2012)
ABSTRACT Gray markets arise when a manufacturer's products are sold outside of its authorized channels, for instance when goods designated by a multinational firm for sale in a foreign market are resold domestically. One method multinationals use to combat gray markets is to increase transfer prices to foreign subsidiaries in order to increase the gray market's cost base. We illustrate that, when a gray market competitor exists, the optimal transfer price to a foreign subsidiary exceeds marginal cost and is decreasing in the competitiveness of the domestic market. However, a multinational's discretion in setting transfer prices may be limited by mandatory arm's length transfer pricing rules. Provided gray markets exist, we characterize when mandating arm's length transfer pricing lowers domestic social welfare relative to unrestricted transfer pricing. We also demonstrate that gray markets can lead to higher domestic tax revenues, even when gray market firms do not pay taxes domestically.